Reduced quality of sterile Queensland fruit fly following post-production stress from hypoxia, irradiation and vibration - Benelli, M.; Mainali, B.; Taylor, P. W.; Rempoulakis, P. (Journal of pest science, 2021)
The sterile insect technique (SIT), a benign pest control strategy, is currently undergoing a substantial renewal for controlling the Queensland fruit fly (Q-fly), a major horticultural pest in Australia. Production and delivery of high-quality flies is fundamental to effective SIT. While efforts are commonly made to improve production at a factory level (both quantity and quality), the methods and conditions during post-production operations also need to be tuned to minimize reductions in fly quality. Hypoxia, irradiation and vibration are important stressors that are experienced by pupae during production, packing and transportation. However, little is known about the impacts of such stressors on Q-fly quality. We conducted two laboratory experiments to investigate the response of Q-fly to such post-production stressors, with the aim of then developing guidelines that minimize quality reductions for SIT programs. In Experiment 1, Q-fly pupae of different ages (3, 6 or 9-day old) were exposed to vibrations for 5, 30, 60 and 300 s. Flight ability tests revealed that 6- and 9-day-old pupae were the most sensitive to vibration, with significant reduction in emergence and percentage of fliers. In Experiment 2, the effect of hypoxia, irradiation and vibration, in isolation or in combination, was evaluated on 9-day-old pupae. Irradiation and vibration exhibited a multiplicative negative effect on flight ability parameters. It is recommended not to subject pupae to intense or extensive vibration during the late pupal stage and to avoid prolonged periods of hypoxia.